Platelet Deposition Onto Vascular Wall Regulated by Electrical Signal - Wang, Mingyan; Zhang, Wei; Qi, Zhi (Frontiers in Physiology, 2021)
Platelets deposition at the site of vascular injury is a key event for the arrest of bleeding and for subsequent vascular repair. Therefore, regulation of platelet deposition onto the injured site during the process of platelet plug formation is an important event. Here we show that electrical signal could regulate the deposition of platelets onto the injured site: the area of platelet deposition was reduced when the cathode of the applied electric field was placed at the injured site before hand, while it was increased when the anode was at the site. On the other hand, if a cathode was placed at the injuried site after the injury, the electrical signal could remove the outer layer of the deposited platelets. Furthermore, electric field could drive rapid platelet deposition onto the blood vessel wall at the site beneath the anode even in uninjured blood vessels. Platelet deposition can thus be manipulated by externally applied electric fields, which might provide a mechanism to manipulate platelet deposition onto the wall of blood vessels.